Sedation strategies for defibrillation threshold testing: safety outcomes with anaesthesiologist compared to proceduralist-directed sedation: an analysis from the SIMPLE study. Issue 11 (6th June 2018) - Sandhu, Roopinder K; Quadros, Kenneth K; Liu, Yan Yun; Glikson, Michael; Kutyifa, Valentina; Mabo, Phillipe; Hohnloser, Stefan; O'Hara, Gilles; VanErven, Liselot; Neuzner, Jorg; Kautzner, Josef; Gadler, Frederik; et al.
Abstract: Aims: No standard practice exists with respect to anaesthesiologist-directed sedation (ADS) vs. sedation by proceduralist (PDS) for defibrillation threshold (DT) testing. We aimed to evaluate adverse events and safety outcomes with ADS vs. PDS for DT testing. Methods and results: A post hoc analysis of the Shockless Implant Evaluation (SIMPLE) study was performed among the 1242 patients who had DT testing (624 ADS and 618 PDS). We evaluated both intraoperative and in-hospital adverse composite events and two safety composite outcomes at 30-days of the main trial. Propensity score adjusted models were used to compute odds ratio (OR) and 95% confidence interval (CI) to evaluate the association between adverse and safety outcomes with method of sedation and independent predictors for use of ADS. Compared to PDS, patients who received ADS were younger (62 ± 12 years vs. 64 ± 12 years, P  = 0.01), had lower ejection fraction (left ventricular ejection fraction 0.31 ± 13 vs. 0.33 ± 13, P  = 0.03), were more likely to receive inhalational anaesthesia, propofol, or narcotics ( P  < 0.001, respectively) and receive an arterial line (43% vs. 8%, P  = <0.0001). Independent predictors for ADS sedation were presence of coronary artery disease (OR 1.69, 95% CI 1.0–2.72; P  = 0.03) and hypertrophic cardiomyopathy (OR 2.64, 95% CI 1.19–5.85; P  = 0.02). Anaesthesiologist directed sedation had higher intraoperative adverse events (2.2% vs. 0.5%; OR 4.47, 95% CI 1.25–16.0; P  = 0.02) and higher primary safety outcomes at 30 days (8.2% vs. 4.9%; OR 1.72 95% CI 1.06–2.80; P  = 0.03) and no difference in other outcomes compared to PDS. Conclusion: Proceduralist-directed sedation is safe, however, this could be result of selection bias. Further research is needed.